THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND ENGLISH ACHIEVEMENT OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT ISLAMIC UNIVERSITY OF MALANG - Luluk Choirun Nisak Nur (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2017)
Abstract This study was aimed to answer a research question, is there any significant correlation between students’ motivation and English achievement at the fourth semester of English department at Islamic University of Malang. This study is classified into descriptive research and for more specific; the researcher used quantitive design, which is correlation study. The procedure of this study used the correlation formula of Person Product Moment. Based on the calculation of this research, the result of correlation between two variables is lower than the critical value. The research hypothesis was rejected and the null hypothesis was accepted. In other words, if this research had used only motivation as independent variable, it would not had significant correlation to the students’ English achievement of the fourth semester students of English department at Islamic University of Malang. Keywords: Correlation, Motivation, Achievement.